The effect of gender orientation on job assignment in broadcast communications industry in Iloilo City - Avelino, Karen Kaye D.; Dasig, Rosemarie Jane P.; Diaz, Gerlie O.; Rabe, Gerda B.
This study aims to find out whether gender orientation affects job assignment in the Broadcast Communication Industry in Iloilo City. In a radio station, there is always a preconceived notion that some departments are only fit for males or females or homosexuals. This study provides an in-depth analysis of the relationship between the dependent and the independent variable as well as the intervening variable which are job assignment, gender, job performance, age, educational attainment, experience, personality and skills and talent respectively. This study is made on the assumption that gender bias exist in any organization specifically in the broadcast communication industry. This assumption is supported by the perception that men are capable than women in terms of physical strength while women should only be limited to administrative positions. There are fifteen stations being studied, six of which are AM Stations and the rest are FM Stations, The researchers made use of questionnaires and interviews as methods for data gathering. The data are then analyzed using the frequency distribution table. It is found out that gender is not the main factor considered by management in assigning job.